Film review. (1st June 2014) - Adeleye, Ifedayo
Tango With Me: A Step Forward with the New Nollywood Film: Tango With Me (2010). 104mins Release Date: 24 August 2012 (UK) Producer/Director: Mahmoud Ali Balogun Author: Dapo Oshiyemi Talking Drum Entertainment Stars include: Joseph Benjamin, Bimbo Manuel, Genevieve Nnaji Production Company: Brickwall Communications Production Cost: 50 Million Naira (estimated cost) Website: http://www.tangowithmefilm.com